From English Gentleman to Spanish hidalgo: Frank Hall Standish (1799–1840) and his Spanish Art Collection - Xanthe Brooke (Boletín del Museo del Prado)
Frank Hall Standish lived in Seville between around 1830 and 1840, during which time he created one of the foremost collections of Spanish art in the city, acquiring some 240 paintings and over 260 drawings – mostly by Spanish masters such as Murillo, Velázquez and Zurbarán. He befriended resident diplomats such as the British vice-consul Julian Benjamin Williams, from whom he acquired some of his collection, and authored several publications, including a travel book on the countries of the Mediterranean, and another on the art and antiquities of Spain (specifically, the art collections of Seville and its hinterlands), which was published shortly before his death in 1840. In the same year, he bequeathed his collection to the French king Louis Philippe I; by 1842 it had been installed as the ‘Musée Standish’ on the top floors of the Louvre, alongside the recently established Galerie Espagnole. Standish’s collection was sold at auction in 1842 and 1853. This article discusses some of its works, and identifies their present locations.